Relativization of Tor for HH of crossed products - Ccolque Taipe, Felipe Clímaco (2022)
In this article, from the relativization of the functor Tor some properties of Hochschild homologies of crossed  products of Hopf are determined. The Hochschild homology functor of a product crossed satisfies the properties of a left satellite relative to an associated projective class of epimorphisms of an additive functor.